Proceso de cobranza y morosidad del impuesto predial de la Municipalidad Distrital de San Juan Bautista año 2025 - Del Castillo Fasabi, Nelly Luz (2025)
The research is based on the study variables defined as the collection process and property tax delinquency. The research methodology was basic, with a quantitative approach, a descriptive-correlational level, and a non experimental, cross-sectional design. The population consisted of 40 employees from the Revenue area of the Provincial Municipality of San Juan Bautista. The sample was a census, including all 40 employees. Descriptive results showed that the collection process was predominantly perceived as "Sometimes" (60%), while property tax delinquency was critically high (78% "Always"). Inferentially, a moderate and significant positive Spearman's Rho correlation of 0.469 was found, with a p-value of 0.002 (which is < 0.05). It was concluded that the obtained results determine a moderate and significant relationship between the variables, leading to the acceptance of the general hypothesis, Hi. This association suggests that current collection management in the District Municipality of San Juan Bautista coexists with property tax delinquency.